Acupuncture Treatment in Clinical Studies for Parkinson's Disease : A Literature Review - Soo Ah Sohn; Kyoung Yun Lee; Chang Wan Kim; Yu Jin Lee (MEDrang Inc., 2018)
Background Parkinson's disease is the second most common degenerative brain disease after Alzheimer's disease. This study reviewed clinical practice of acupuncture and moxibustion treatment for Parkinson's disease to assess the future direction of these treatments. Methods The literature search used 5 Korean Internet databases. The search terms were "Parkinson's disease." and "Parkinson (Korean)." 36 papers were selected: 27 case reports, 2 respropective studies, 3 uncontrolled clinical trials, 3 randomized controlled trial, 1 non-randomized controlled trial. Results Filiform needles were used in most of studies. Pharmacopuncture, electro-acupuncture, and auricular acupuncture therapy were also used in combination with Filiform needles. 2. The most commonly used basic acupoints for Parkinson's disease was Saamchimbeop. The most commonly used form of pharmacopuncture involved Bee-venom. Conclusions It is expected that treatment of Parkinson's disease with a variety of acupuncture and moxibustion therapies will continue to be studied, in addition to treatments that utilize existing Filiform needle treatments in clinical practice.